2016
DOI: 10.1007/s11105-016-0985-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between H2O2 in Polyamine Metabolism and Lignin in the Exocarp of a Russet Mutant of ‘Dangshansuli’ Pear (Pyrus bretschneideri Rehd.)

Abstract: The fruit of the 'Dangshansuli' pear has a greenish yellow skin, whereas its mutant, the 'Xiusu' pear, has a russet skin, which represents a genetic variation. It has been demonstrated that the formation of russet fruit in the 'Xiusu' pear is related to lignin accumulation in skin exocarp cells. In this study, we localized hydrogen peroxide (H 2 O 2 ) to the cell wall using transmission electron microscopy (TEM) and quantified the concentrations of H 2 O 2 and polyamines. In addition, the expression levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…Studies on pears and apples have highlighted that lignin synthesis genes, such as COMT and C4H, have increased expression, underlying the lignin accumulation that leads to russet formation [5,27]. Studies on 'Dangshansu Pear' mutant varieties have shown that increased expression of CCoAOMT leads to an increase in the lignin content of the outer peel, which results in russet formation [28]. Similar results were observed in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Studies on pears and apples have highlighted that lignin synthesis genes, such as COMT and C4H, have increased expression, underlying the lignin accumulation that leads to russet formation [5,27]. Studies on 'Dangshansu Pear' mutant varieties have shown that increased expression of CCoAOMT leads to an increase in the lignin content of the outer peel, which results in russet formation [28]. Similar results were observed in this study.…”
Section: Discussionsupporting
confidence: 87%
“…It also increases parthenocarpic fruit set in apple (Watanabe et al 2008) and extends the shelf-life of grape and blueberry (Nesmith 2002). Limited studies have been conducted to address the russet problem in 'Shine Muscat' grapes by applying different concentrations of GA 3 and CPPU to gain insight into the molecular mechanism underlying fruit russet (Wang, Li, et al 2014;Heng et al 2016;Liang et al 2016;Wang et al 2017). The present study is the first one to simultaneously explore the physiological and molecular mechanisms associated with the russet problem in grape berries.…”
Section: Discussionmentioning
confidence: 94%
“…Russet skin is a vital trait affecting both fruit quality and stress tolerance in pear. Although several studies on russet pear have enabled a better comprehension of the mechanical causes responsible for this phenomenon ( Heng et al, 2016 ; Shi et al, 2019b ), the genetic and molecular mechanisms underpinning russet skin coloration have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that lignin biosynthesis can regulate russet skin formation in the russet skin mutant DSS of pear ( Heng et al, 2016 ). Here, we observed considerably higher lignin contents in russet skin fruits than in non-russet skin fruits ( Figure 1C ), yet chlorophyll contents were not significantly different between the two fruit types ( Figure 1B ).…”
Section: Discussionmentioning
confidence: 99%